O aprisionamento da mulher: The Handmaid’s Tale na contemporaneidade - Paula, Luciane de [UNESP]; Batista, Rafaela dos Santos [UNESP] (Programa de Estudos Pós-graduados em Comunicação e Semiótica - PUC-SP, 2022)
This article analyzes, through the bakhtinian method, the TV series The Handmaid’s Tale (2017, 2018, 2019) in comparison with Porta dos Fundos’ sketch Handmaid’s Tale (2019), which makes references to Brazilian politics scenario. This work’s aim is to reflect on: how present the discourse depicted in the TV show is; the value attributed to women and the relation between the TV series and Brazilian society. This paper is based on bakhthinian studies. In order to exemplify the relation between Brazilian society and the TV series, two Instagram posts will be analyzed. This study is justified by its social relevance. The results show how the current Brazilian government intensifies inequality through its patriarchal practices, which are sustained by religious discourses.

Este artigo analisa, com base no método bakhtiniano, o enunciado estético do seriado The handmaid’s tale (2017, 2018, 2019), em cotejo com o esquete do Porta dos fundos, denominado Handmaid’s tale (2019), relacionado à política brasileira. Os objetivos são refletir sobre: a atualidade do discurso da série; a valoração da mulher; o seriado relacionado à sociedade brasileira. Os estudos bakhtinianos fundamentam esta escrita e a relevância social justifica o estudo. Para exemplificar a relação com a sociedade brasileira, como cotejo, são trabalhados dois posts do Instagram. Os resultados revelam quanto o atual governo intensifica as desigualdades, com suas práticas patriarcais, sustentadas pelo discurso religioso.
The imprisonment of women: The Handmaid’s Tale in contemporary times
Keywords: Bakhtin Circle; gender; patriarchy; art and life; woman; Círculo de Bakhtin; gênero; patriarcado; arte e vida; mulher